Pengembangan Strategi Pemasaran Digital terhadap Penjualan Produk Peralatan Rumah Tangga di Toko Mekar Bireuen - Zuriani Ritonga; Fatimah Zuhra; Afriana Afriana; Rara Astili Siregar (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to analyze effective digital marketing strategies in increasing sales of household appliance products at Toko Mekar. The growth of digital technology has changed the business landscape, and businesses must adopt relevant marketing strategies to stay competitive. Through a qualitative approach, data is collected through in-depth interviews with Store owners who have implemented digital marketing strategies. The analysis was conducted to identify patterns, challenges, and successes in implementing the strategy. The findings show that those who implement digital marketing strategies well tend to have a significant increase in their sales. Factors such as a good understanding of the target market, creativity in content, and the appropriate use of digital platforms have proven to be effective in increasing the visibility and appeal of products on their stores. This research provides valuable insights for business actors and other stakeholders about the importance of digital marketing strategies in increasing business competitiveness and growth in the digital era.